The Effect of Papaya Leaf Concentration and Fermentation Time on The Decafeination Process of Robusta Coffee - Tri Hariyadi; Keryanti Keryanti; Nurisa Salsabila; Sarah Sarah (Fluida, 2023)
High level of caffeine in Robusta coffee requires the reduction of level to accommodate person with low caffeine tolerance. The wet fermentation process with papaya leaf extract containing the papain enzyme was used to decaffeinate the coffee. This study aimed to investigate the effects of papaya leaf extract concentration and sampling time on the decaffeination of Robusta coffee green beans. The papaya leaf extract concentration ranged from 10% to 80% (w/v), with fermentation lasting 6 to 72 hours. The caffeine content was measured using a UV-Vis spectrophotometer, and organoleptic tests were performed on 40 untrained panelists. The results showed that both the concentration of papaya leaf extract and the fermentation time influenced the decaffeination. The optimum result was obtained after 48 hours of fermentation with 80% (w/v) papaya leaf extract resulting in a caffeine content of 0.268% (w/w) from an initial content of 1.20% (w/w), representing a 77.82% decrease in caffeine level efficiency. Fermented coffee was preferred by 58% of panellists over unfermented coffee. These findings imply that papain found in papaya leaves can reduce caffeine levels while also improving flavor and aroma.